The spaced learning concept in combination with halsted and peyton - a randomized controlled study - Le, Melanie Thanh Phuong; Boettcher, Johannes; Vincent, Deirdre; Elrod, Julia; Mietzsch, Stefan; Romero, Philipp; Perez, Anna; Reinshagen, Konrad; Boettcher, Michael (Journal of surgical education, 2022)
BACKGROUND - Several motor learning models have been used to teach highly complex procedural skills in medical education. Two approaches are often employed amongst health care professionals: Halsted's “See one - do one - teach one” concept and Peyton's Four-step approach. Peyton's deconstruction of the learning process into 4 sub-steps was reported to be preferable for learning/acquiring/teaching complex clinical skills. However, a new increasingly popular technique is known as the spaced learning method. In a previous study, we were able to confirm that the spaced learning concept is superior for laparoscopic suturing and knot tying compared to conventional training curricula, this current study aimed to assess the influence of spaced learning in combination with Halsted's and Peyton's tutoring approaches on laparoscopic knot tying of medical students. - METHODS - After randomization, 20 medical students were either assigned to Halsted's or Peyton's teaching approach and trained one-on-one (teacher-student). Additionally, all subjects were trained according to the spaced learning concept, containing 40 minutes of content-blocks, followed by a 20-minute break involving coordinated, standardized physical activity. This was repeated three times. Primary endpoints were time, knot quality, precision, knot strength, as well as overall laparoscopic knotting performance and competency. To evaluate the motivation of the subjects, an 18-item questionnaire was utilized to measure four motivational factors (anxiety, probability of success, interest, and challenge). - RESULTS - All trainees significantly improved after training in all knot attributes. Trainees assigned to Halsted's method were able to significantly outperform the Peyton group in knot quantity within 30 minutes (p=0.013), time/knot (p=0.033), performance score (p=0.009), and precision (p=0.032). No significant difference between Halsted and Peyton was found for knot strength and quality. Furthermore, no significant difference was identified comparing motivation pre- and post-training. However, subjects in the Peyton appeared to be significantly more anxious after training. - CONCLUSION - Combining spaced learning technique with Halsted's “see one - do one - teach one” appears to be superior to Peyton's Four-step approach in conjunction with spaced learning in surgical naïve students. We recommend further studies evaluating the combination of spaced learning with Halsted and Peyton's instructional methods.